2019
DOI: 10.12688/gatesopenres.12953.2
|View full text |Cite
|
Sign up to set email alerts
|

Developing acceptable contraceptive methods: Mixed-method findings on preferred method characteristics from Burkina Faso and Uganda

Abstract: Background: Unmet need remains high in developing regions. New contraceptive technologies may improve uptake and use. This study examines desirable product characteristics. Methods: We added a module to the female questionnaire of the PMA2020 surveys in Burkina Faso and Uganda and conducted 50 focus group discussions (FGDs) with women, 10 FGDs with men, and 37 in-depth interviews (IDIs) with providers across the two countries. FGDs with women and IDIs with providers included a semi-structured ranking exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…The larger research was focused on collecting attitudes on specific contraceptive method attributes; reactions to six new contraceptive methods in development; and reasons for method preference among women, men, and family planning providers and program staff. 19,20 Married women in both Burkina Faso and Uganda had rates of modern contraceptive use close to the average rates in Western and Eastern Africa at the time of the original study (25% and 32%, respectively); 21,22 some 3% used male condoms in Burkina Faso and 6% used them in Uganda. In this article, we analyzed the data gathered through focus groups to explore support among men and women for male-directed contraceptive methods, to identify potential facilitators and barriers to using new male methods, and to gain insight into desirable characteristics of these methods.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The larger research was focused on collecting attitudes on specific contraceptive method attributes; reactions to six new contraceptive methods in development; and reasons for method preference among women, men, and family planning providers and program staff. 19,20 Married women in both Burkina Faso and Uganda had rates of modern contraceptive use close to the average rates in Western and Eastern Africa at the time of the original study (25% and 32%, respectively); 21,22 some 3% used male condoms in Burkina Faso and 6% used them in Uganda. In this article, we analyzed the data gathered through focus groups to explore support among men and women for male-directed contraceptive methods, to identify potential facilitators and barriers to using new male methods, and to gain insight into desirable characteristics of these methods.…”
mentioning
confidence: 84%
“…The methodology for this study has been described in detail elsewhere. 19,20 To be eligible to participate, women had to be aged 15-17 and married or aged 18-49, while men had to be 18 or older. One woman aged 50 participated in the study; no man younger than 23 did so.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“… 49 One recent study found that 65% of women in Burkina Faso and 40% of women in Uganda would use a method that pauses bleeding. 52 Adolescents and young adults may be especially interested in limiting or controlling the timing of menstruation with hormonal contraception. 53 , 54 …”
Section: Biological Linkages Between Mh and Srhrmentioning
confidence: 99%
“…49 One recent study found that 65% of women in Burkina Faso and 40% of women in Uganda would use a method that pauses bleeding. 52 Adolescents and young adults may be especially interested in limiting or controlling the timing of menstruation with hormonal contraception. 53,54 Various factors may contribute to an individual's preferences for or willingness to tolerate changes to normal bleeding patterns, including age, region, marital or cohabitation status, previous use of hormonal contraception, experience of menstruation, desire to prevent pregnancy and individual and cultural attitudes and beliefs about menstruation.…”
Section: Menstrual Disordersmentioning
confidence: 99%